The “PIP scandal” – Complications in Breast Implants of Inferior Quality: State of Knowledge, Official Recommendations and Case Report - Lampert, F. M.; Schwarz, M.; Grabin, S.; Stark, G. B. (Geburtshilfe und Frauenheilkunde, 2012)
Following the clinical observation of high rate of ruptures of breast implants of the French manufacturer Poly Implant Prothèse (PIP), the French Health Products Safety Agency (Afssaps) removed these products from the market in March 2010. Physical and toxicological tests confirmed the use of silicone of improper quality both for the shell and the gel filling. Until now (12/2011), no acute toxicity or mutagenicity could be observed, but 20 cases of malignancies occured in carriers of PIP-prostheses. By means of a clinical example, we summarize the official recommendations of the Afssaps and its German equivalent, the Bundesinstitut für Arzneimittel und Medizinprodukte (BfArM) for diagnosis and treatment in women with PIP breast implants. Furthermore, we intend to raise awareness for the fact that the German GfE Medizintechnik and the Dutch manufacturer Rofil distributed the identical product with a different label. Supplementary, the medical and medico-legal aspects of the “PIP scandal” are discussed.
Keywords: benign mammary gland tumor; BRCA (breast cancer antigen); breast; mammary gland tumor; mammary malformation